Electronic Lesson Development: Mathematics for ‘Long Lap Lae’ Durian Agricultural business in Uttradit Province: A Case Study of Moderate Class-More Knowledge Policy in Schools - ปัญญายง, ทวีสิทธิ์ (Ratchaphruek Journal, 2018)
ABSTRACT This semi experimental research aimed to 1) develop and validate the efficiency mathematical electronic lessons for Durian business, Long Lap Lae, Uttradit province conduced to different schools according to moderate class, more knowledge policy in gaining the efficiency (E1/E2) to the criteria 80/80, 2) study the learning achievement of students before and after the lessons, and 3) study the students’ satisfaction towards the electronic lessons. Research samples were divided into 2 groups; 1) 100 durian ‘Long Lap Lae’ farmers were selected for gathering information in order to design the lessons, and 2) 77 secondary students were selected to implement the lessons. Both sample groups were obtained by purposive sampling technique. Research instrument comsisted of 1) 8 units of electronic lessons, 2) an in-depth interview questionnaire, 3) an achievement test, and 4) a students’ satisfaction survey. Statistics used were mean, percentage, standard deviation, and t-test. The result showed that the efficiency of the mathematical electronic lessons for Durian business ‘Long Lap Lae’, conduced to schools had the efficiency of in-class activities (E1) and post-test (E2) at 92.26/88.65 The students’ post test scores showed the learning achievement were significantly higher than the pre test scores at .01 level. Moreover, the students’ satisfaction towards the lessons was at high level.